The vertical profile of chlorophyll-a in pinang dalam lake Buluh cina village siak hulu subdistrict kampar district Riau province - Arum Fuji R Manurung; Madju Siagian; Clemens Sihotang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research has been done in the Pinang Dalam Lake Buluh Cina Village SiakHulu Subdistrict Kampar District Riau Province. This research aims to understand thevertical profile of chlorophyll-a in this lake. The research used survey method. Thechlorophyll-a samples were collected from three station namely station I at inlet of lake ,station II in the midle of lake and station III the end of lake. There were three samplingsites in each station were in the surface, 1.5 Secchi depth and 2.5 Secchi depth. Samplingwas done three times, once a week. The result shown chlorophyll-a concentration insurface :17.26 μg/L -21.44 μg/L, 1.5 secchi depth 11.60 μg/L-14.43 μg/L and in 2.5 secchidepth 9.98 μg/L - 12.41 μg/L. A chlorophyll-a concentration in surface higher than in the1.5 secchi depth and 2.5 secchi depth. The chlorophyll-a concentration decrease with thedepth. Water quality result shown pH:5; DO: 2.60-5.88 mg/L; CO2: 6.79-13.31 mg/L;nitrate: 0.0134-0,093 mg/L; phosphate: 0.03-0.15 mg/L; phytoplankton abundance:3,420,423-4,293,075 cell/L; depth: 180.67-429 cm; transparency: 52.5-54.5 cm;temperature: 28oC-28.34oC. Based on data obtained, it can be concluded the consentrationof chlorophyll-a in Pinang Dalam Lake showed the trophic status was mesotrophic and allwater quality still support the life of aquatic organisms.Keywords : Chlorophyll-a, the vertical profile, Pinang Dalam Lake